PENGARUH MODEL PEMBELAJARAN SIKLUS TERHADAP KEMAMPUAN APRESIASI PUISI DI KELAS VII SMP NEGERI 2 INDRAMAYU TAHUN PELAJARAN 2013/2014 - Dede Endang Mascita; Iyay Robia Khoerudin; Johar Maknun (Program Studi Pendidikan Bahasa Indonesia Pascasarjana UGJ, 2015)
This study focused on teaching model cycle capability poetry appreciation. This study aimed to describe the process of learning by using learning model cycle. Describe the activity of students in the learning cycle to learning poetry appreciation by applying the 5 stages: (a) generating interest (enggament), (b) exploration ( Exploration), (c) an explanation (explanation), (d) elaboration (elaboration), and evaluation (evaluation), and determine the effect on the ability of learning model cycle appreciation of poetry.Based on the results of this study concluded 1) The process of learning poetry appreciation by applying the learning model cycle can improve student learning outcomes. 2) Activity of students in learning poetry appreciation by using the model of the cycle of learning can help students actively learn independently in groups , solve the problem of learning. Applying learning model cycle can assist students in learning menningkatkan understanding. 3) learning model cycle affect the ability of appreciation of poetry and effective against the appreciation of poetry. Applying learning model cycle is expected to help teachers and students to improve the quality of teaching so that learning objectives can be achieved the expected goals.The data in this study of student understanding of the appreciation of poetry that includes elements that build the poem with assessment criteria include a general overview of the contents of understanding aspects of poetry, pemhaman tone, understanding feeling / sense, image understanding, understanding the style of language, understanding the message, understanding the content of the poem in life.To test the hypothesis based on the assumption that different test results obtained from the initial ability appreciation of poetry and learning achievement as indicated by the value of pretest and post-test that includes testing the experimental classes and control classes.Based on the analysis there are differences in pretest and post-test results of the experimental class, which is the result of the analysis, sig ( 2 - tailed ) < 0.05, then Ho is rejected and Hi which is the research hypothesis is accepted that effective learning model cycle of the ability of appreciation of poetry.Applying learning model cycle is expected to help teachers and students to improve the quality of teaching so that learning objectives can be achieved.